Affirmative Action Model in Strengthening the Education Rights Protection and Fulfillment of Person with Disability - Mohamad, Irwansyah Reza; Hadi, Ismet (International Journal Papier Public Review, 2021)
The uncertainty of legal regulations on the fulfillment of education rights for persons with disabilities creates serious problems. The absence of special arrangements causes overlapping responsibilities which will result in not being integrated into programs that support the educational needs of persons with disabilities. This problem requires the seriousness of local governments to provide protection and fulfillment of education rights for persons with disabilities. This study aims to determine the legal policy for the Protection and Fulfillment of the Right to Education and to formulate an affirmative action model for the protection and fulfillment of the education rights of persons with disabilities in the future. This study uses empirical legal research, namely research that initially examines secondary data, then continues with research on primary data through interview data collection. The results of the research show that local governments still seem to have not fully provided protection and fulfillment of the rights of persons with disabilities to adequate education so that they face various kinds of discrimination, even though there are regulations at the level of the 1945 Constitution of the Republic of Indonesia and laws that have guaranteed it. Second, regulations at the level of Regional Regulations in Gorontalo Province have not reached the lateness of fulfilling the right to education both inclusively and specifically in a systematic and comprehensive manner. It is necessary to have a legal reform in the form of affirmative policies in the field of education for persons with disabilities.